Navigating Cancer with Emotional Intelligence: A Study on Self-Care Behavior Enhancement in Women - Yosefi, Asra; Azimi ferydni, Majid; Mokhtari, Hoseyn (Psychology of Woman Journal, 2023)
Objective: This study aimed to evaluate the effectiveness of an emotional intelligence (EI) training program in improving self-care behaviors among female cancer patients. It hypothesized that participants undergoing the EI training would exhibit significant improvements in self-care behaviors compared to those in the control group. Methods and Materials: Employing a randomized controlled trial design, this study involved 30 female cancer patients, divided equally into an experimental group, which received the EI training, and a control group, which did not receive any intervention. The EI training was structured into 8 sessions, each lasting 90 minutes, spread over 8 weeks. Self-care behavior was measured using the Self-Care of Chronic Illness Inventory (SC-CII) at three time points: baseline, post-intervention, and at a four-month follow-up. Findings: The findings revealed that the experimental group showed a significant improvement in self-care behaviors from baseline to post-intervention and maintained these improvements at the four-month follow-up. Analysis of variance with repeated measurements indicated significant effects for time, group, and the interaction between time and group on self-care behavior scores, demonstrating the positive impact of EI training. Conclusion: The study concluded that emotional intelligence training significantly enhances self-care behaviors among female cancer patients. These improvements were sustained over time, highlighting the potential of EI training as a valuable intervention in the supportive care of cancer patients. The findings suggest the integration of EI training into patient care programs could be beneficial in improving the quality of life and well-being of individuals facing the challenges of cancer.